Prior oral proton‐pump inhibitor use is associated with reduced severity of aspirin‐related upper gastrointestinal bleeding in older people. Issue 4 (13th April 2022) - Ayonrinde, Oyekoya T.; Walldorf, Natasha; Chan, Nicholas; Foo, Nathanael Y.; Kulkarni, Tithi; Olynyk, John K.; Sanfilippo, Frank M.
Abstract: Low‐dose aspirin is commonly used for primary or secondary prophylaxis against cardiovascular disease in older people. However, the potential risk of upper gastrointestinal (UGI) ulceration and bleeding associated with low‐dose aspirin use is often not appreciated by prescribers and older consumers. Among 133 serial patients with UGI bleeding, aspirin‐users aged ≥70 years had a ninefold increased likelihood of overt UGI bleeding compared with non‐users, reducing by 90% in regular proton‐pump inhibitor users (adjusted odds ratio 0.10). We recommend risk‐versus‐benefit discussions when recommending aspirin to older people.